2007
DOI: 10.1111/j.1574-6968.2006.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Oryza sativa rice plants contain molecules that activate different quorum-sensing N-acyl homoserine lactone biosensors and are sensitive to the specific AiiA lactonase

Abstract: Gram-negative bacteria most often use N-acyl homoserine lactones (AHLs) as intercellular quorum-sensing signal molecules. In this study, it was demonstrated that rice plants contain AHL mimic molecules that are very sensitive to the highly specific AiiA lactonase enzyme and can activate three different AHL bacterial biosensors, indicating that the compounds have a homoserine lactone structure and could be AHLs. The possible source and biological significance of this finding are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 40 publications
(68 reference statements)
1
23
0
1
Order By: Relevance
“…Both plants and algae have been shown to produce and secrete compounds that mimic quorum sensing components and inXuence bacterial gene expression Degrassi et al 2007). In addition, plants seem to be able to detect various AHLs at quite low concentrations (Mathesius et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Both plants and algae have been shown to produce and secrete compounds that mimic quorum sensing components and inXuence bacterial gene expression Degrassi et al 2007). In addition, plants seem to be able to detect various AHLs at quite low concentrations (Mathesius et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The interference with bacterial signaling by excreting QS-mimic orinhibitory substances would have the advantage to disturb the coordination of the bacterial attackespecially in the case of pathogens. It has been indeed found in several plants, that QS-inhibitors are produced (Bauer and Mathesius 2004;Degrassi et al 2007;Hentzer et al 2002;Rasmussen et al 2005;Teplitski et al 2000). On the other hand, it was demonstrated that mostly leguminous plants are able to degrade bacterial N-acyl homoserine lactone (AHL) autoinducers by excreting lactonases or AHL-hydrolases (d' AngeloPicard et al 2005;Delalande et al 2005).…”
Section: Exudation Of Antimicrobialsmentioning
confidence: 99%
“…Several plant species secrete AHL mimics which can either stimulate or inhibit bacterial AHL QS systems (Bauer and Mathesius, 2004). Detection of AHL mimics have been reported in secretions of pea, rice, soyabean, tomato, crown vetch, M. truncatula, and from the unicellular algae Chlamydomonas reinhardtii (Degrassi et al, 2007;Gao et al, 2003;Teplitski et al, 2004;Teplitski et al, 2000). No evidence is currently available that these AHL mimics are interacting with QS systems in vivo; experiments in tomato with A. tumefaciens, in fact, have evidenced that these mimics cannot act as AHL agonists (Khan and Farrand, 2008).…”
Section: Plant Interkingdom Signaling With Bacterial Ahl Quorum Sensingmentioning
confidence: 99%